A standards-based evaluative analysis of the effectiveness of the Arabic language learning assessment system for eighth-grade students in Arabic schools in Brunei Darussalam - Yani, Achmad; Haji Ahmad, Siti Sara; Haji Abdullah, Hajah Rafidah; Abdul Karim, Norhayati; Mohamed Abdelgelil, Mohamed Fathy; Sef, Faisal Mubarak; Sahrir, Muhammad Sabri; Haji Abdullah, Hajah Rafizah; Husain, Muhammad Zakir; Mohamed Mousa, Abdelnaser Abdelgalil (WSEAS Press, 2026)
This study aimed to analyze the effectiveness of the Arabic language learning assessment system for eighth-grade students in Arabic schools in Brunei Darussalam in light of global standards for language assessment, with particular emphasis on validity, comprehensiveness, alignment, and balance across the four language skills. The study adopted a mixed-methods approach using an explanatory sequential design. Quantitative data were collected from 201 students through a five-point Likert-scale questionnaire, and the findings were subsequently enriched by qualitative evidence derived from semi-structured interviews with 15 teachers, document analysis, and classroom observations. Quantitative data were analyzed using percentages and relative weights, whereas qualitative data were examined through thematic analysis. The findings revealed that the assessment system demonstrates a generally good level of overall effectiveness, albeit with noticeable variation across its components. Writing emerged as the most strongly assessed skill (80.2%), followed by reading (78.9%), speaking (76.2%), and listening (74.5%), indicating a relative preference for written over oral skills. The results further showed a good level of test validity (81.2%) and alignment with curricular content (77.7%), alongside the continued dominance of grammar-based questions (82.1%), a relative imbalance between theoretical and practical dimensions (67.8%), and a limited presence of diagnostic assessment (63%). The study underscores the need to develop the assessment system toward a more communicative and integrated model that strengthens performance-based and formative assessment and measures learners’ actual linguistic competence in a more comprehensive manner